Association of circulating IL-6 and IL-10 levels during mid-gestation with recurrent pregnancy loss history and severity: a South Indian study - Sufaya Jameel; Rashmi Bhuwalka; Parveen Jahan (Exploration of Immunology)
Aim: Recurrent pregnancy loss (RPL) is defined as the loss of two or more clinical pregnancies before the 20th week of gestation. Globally, RPL affects 1–5% of couples, with approximately 50% of cases remaining idiopathic. This study aimed to assess the circulating levels of interleukin-6 (IL-6) and IL-10 cytokines in pregnant women with and without a history of RPL. Methods: A total of 170 pregnant women in their second trimester with and without a history of RPL were enrolled from Niloufer Hospital, South India. Serum samples isolated from blood were analyzed using a sandwich-enzyme linked immunosorbent assay (ELISA) to estimate IL-6 and IL-10 levels. Results: The median age was significantly higher in the RPL group (25 years) compared to the non-RPL (NRPL) group (22 years) (p = 0.0001). Similarly, body mass index (BMI) was significantly elevated in the RPL group (25.64 kg/m2) vs. the NRPL group (22.51 kg/m2) (p = 0.0001). The analysis revealed significantly elevated IL-6 and reduced IL-10 levels in the RPL group compared to the NRPL group (p = 0.0001). Additionally, the IL-6/IL-10 ratio differed significantly between the two groups. Receiver operating characteristic (ROC) curve analysis indicated that IL-6 was a better marker for RPL than IL-6/IL-10 ratio and IL-10. IL-10 levels were found to be a reliable marker in relation to the extent of pregnancy loss history. Conclusions: The study highlights the presence of a pro-inflammatory systemic milieu in mid-gestation among women with a history of RPL, potentially reflecting the immunological environment at the feto-placental interface. Further research to establish a distinct cytokine signature between RPL and NRPL groups may facilitate the development of targeted preventive and therapeutic strategies. However, the current findings are limited by a modest sample size and a homogenous ethnic population, which may affect generalizability. Larger, multi-ethnic studies are warranted to validate these observations and enhance clinical applicability.